Epigenetic control of phospholipase A2 receptor expression in mammary cancer cells. Issue 1 (December 2015) - Menschikowski, Mario; Hagelgans, Albert; Nacke, Brit; Jandeck, Carsten; Sukocheva, Olga; Siegert, Gabriele
Abstract Background It has recently been proposed that the M-type phospholipase A2 receptor (PLA2R1) acts as a tumour suppressor in certain malignancies including mammary cancer. Considering that DNA methylation is an important regulator of gene transcription during carcinogenesis, in the current study we analyzed the PLA2R1 expression, PLA2R1 promoter methylation, and selected micro RNA (miRNA) levels in normal human mammary epithelial cells (HMEC) and cancer cell lines. Methods Levels of PLA2R1 and DNA methyltransferases (DNMT) specific mRNA were determined using real-time RT-PCR. Methylation specific-high resolution melting (MS-HRM) analysis was utilized to quantify the methylation degree of selected CpG sites localized in the promoter region of thePLA2R1 gene. Expression of miRNA was tested using miScript Primer Assay system. Results Nearly complete methylation of the analyzedPLA2R1 promoter region along withPLA2R1 gene silencing was identified in MDA-MB-453 mammary cancer cells. In MCF-7 and BT-474 mammary cancer cell lines, a higher DNA methylation degree and reduced PLA2R1 expression were found in comparison with those in normal HMEC. Synergistic effects of demethylating agent (5-aza-2′-deoxycytidine) and histone deacetylase inhibitor (trichostatin A) on PLA2R1 transcription in MDA-MB-453 cells confirmed the importance of DNA methylation and histone modification in the regulation of thePLA2R1 gene expression in mammary cells. Furthermore, significant positive correlation between the expression of DNMT1 andPLA2R1 gene methylation and negative correlation between the cellular levels ofhsa-mir-141, −181b, and -181d-1 and the expression of PLA2R1 were identified in the analyzed cells. Analysis of combined z-score ofmiR-23b, −154 and -302d demonstrated a strong and significant positive correlation with PLA2R1 expression. Conclusions Our data indicate that (i) PLA2R1 expression in breast cancer cells is controlled by DNA methylation and histone modifications, (ii) hypermethylation of thePLA2R1 promoter region is associated with up-regulation of DNMT1, and (iii)hsa-miR-23b, −154, and −302d, as well ashsa-miR-141, −181b, and −181d- 1 are potential candidates for post-transcriptional regulation of PLA2R1 expression in mammary cancer cells.